Effect of Metallic Nanocoatings Deposited on Silicon Oxide on Wetting by Filler Melts II. Effect from the Annealing of Nanocoatings Deposited on SiO2 on their Structure and Interaction with the Oxide - Krasovskyy, V.P.; Kostyuk, B.D.; Gab, I.I.; Krasovskaya, N.A.; Stetsyuk, T.V. (Powder metallurgy and metal ceramics, 2020)
The sessile drop method using capillary melt cleaning was employed in the experiment to study the effect of metallic nanocoatings (single Ti, Nb, and Mo coatings and binary Ti–Cu, Nb–Cu, and Mo–Cu coatings with a copper layer of constant thickness) on the wetting of silicon oxide by Pb–15 wt.% In melt in 1 ∙ 10 –3 Pa vacuum at 500°C after their annealing at 900°C. The metallic coatings were applied by electron beam evaporation in vacuum. The binary coatings were produced by sequential deposition of layers. The dependences of contact angle on coating thickness show that the ‘threshold’ thickness is determined by the annealing temperature of the coating or, in other words, its structure. The threshold coating thickness for different metals depends on their chemical affinity to oxygen. When freshly applied and annealed single Mo, Nb, and Ti coatings are wetted, their threshold thickness increases from 70 to 80 nm for the titanium coating, from 63 to 70 nm for the niobium coating, and from 50 to 60 nm for the molybdenum coating. The structure of Cu, Ni, Mo, Cr, Nb, and Ti coatings annealed at 600, 900, and 1200°C was studied. The initial (freshly deposited) metallic coatings showed high integrity. The coatings became dispersed after annealing and their integrity decreased with increasing temperature. The dispersed metallic coatings formed ‘islands’ of various shapes, round shape being predominant, depending on the chemical affinity of the coating metal to oxygen. The so-called ‘solid’ wetting was observed. The shape of the islands is determined by equilibrium between the metal–substrate attraction forces (interaction, adhesion) and the very strong surface tension of the metal (at such a small coating thickness). To use metallic coatings for brazing quartz with aluminum alloys, coatings of adhesive metals (Mo, Cr, Nb, Ti) should be annealed at temperatures of 900–1000°C with a holding time of 10 min. The coating thickness should be within the threshold range.